Growing Stress Among Doctors in India - Dr. Amey Chugh, Dr. Aneesha Nallapati (South Eastern European Journal of Public Health, 2025)
Background and Rationale [1,3] Over the years, the role of doctors in India has become increasingly complicated. While the fundamental duty of saving lives remains the same, the external pressures have multiplied. One such challenge arises from the ever-present risk of litigation in the event of a patient’s death or harm. Despite obtaining informed consents and thoroughly explaining the risks of complex procedures, many doctors have found themselves facing legal battles due to unfortunate outcomes. In the absence of robust legal provisions that safeguard medical practitioners acting in good faith, the threat of lawsuits stands as a major cause of psychological distress. Additionally, the alarming incidents of physical abuse from distressed patients or their relatives highlight an urgent need to address the lack of tangible protections for doctors. These episodes, often captured in media reports, not only inflict bodily harm but also engender deep-seated fear and anxiety in those expected to deliver compassionate care. Such hostility erodes the doctor-patient relationship and deters many from entering or continuing in the medical field. Work Environment and Compensation [2] The conventional image of a medical professional working long and selfless hours remains largely intact. However, this dedication comes at a steep price: lack of job security, insufficient compensation, and erratic schedules that leave little room for rest or personal life. Many doctors endure extremely long shifts, often extending beyond 24 hours, especially during residency or in government-run hospitals—environments that are typically understaffed. The “on-call” nature of medical practice compounds this stress, as emergencies can occur at any hour. Furthermore, salary structures and overall compensation packages for doctors in India can pale in comparison to those abroad. This financial disparity, coupled with the weight of educational loans—often significant due to high tuition fees in private medical colleges—pushes many doctors to seek opportunities overseas, where they find better pay, clearer legal protections, and a generally higher level of respect for the profession. Declining Respect and Its Implications [4] It is disheartening to note that the respect once traditionally accorded to doctors appears to be diminishing. While there may be multiple factors driving this shift in perception, there is a noticeable erosion of trust in the medical community. The growing commercialization of healthcare, miscommunication, and occasional reports of unethical practices have negatively influenced public opinion. However, it is equally vital to acknowledge that the vast majority of doctors strive to maintain high ethical standards, often under extreme pressure. This decline in respect, combined with strenuous working conditions, has had tangible consequences on medical education. Both MBBS (Undergraduate) and postgraduate seats are increasingly going vacant. The reasons are manifold: exorbitant tuition fees deter students who do not have sufficient financial backing, and the observed mental and physical toll on practicing doctors discourages prospective candidates from pursuing a medical career. As a result, India may soon face a deficit of qualified medical professionals, a situation that not only impacts the healthcare system but also endangers patient care. Conclusion [4,5] Doctors are the backbone of any healthcare system. When they are overworked, underprotected, and undervalued, the entire structure of public health and patient care can suffer. By looking at the magnitude of these stressors and their direct effect on both doctors and the broader healthcare framework, we hope to spur a meaningful change. We earnestly believe that more equitable policies, robust legal protections, and supportive work environments are crucial to sustaining the medical profession and ensuring the well-being of future generations.